(590) Note on Statistical Methods ملاحظات حول الطرق الإحصائية - Mahmoud, Moharram (معهد التخطيط القومى, 2024)
The study covers fundamental concepts in statistics, starting with moments around the origin and the mean, including measures of skewness and kurtosis. It also includes basic definitions of probability, conditional probability, and random variables, focusing on discrete and continuous distributions. The emphasis is on probability distributions like the Poisson and binomial distributions, explaining their fitting and applications. Additionally, it discusses estimation and hypothesis testing, including sampling distributions and statistical hypothesis testing. The text further explores analysis of variance and simple and multiple linear regression, detailing how to test the significance of coefficients and related estimates.